Ausgewählte Aspekte der Textsorte autographes Vorwort einer wissenschaftlichen Abhandlung im Deutschen und Polnischen - Versuch einer Konfrontation - Mikołajczyk, Beata (Glottodidactica, 2007)
The purpose of this article has been to compare texts of forewords in Polish and German scientific monographs. The analysis has focused on the following selected aspects: the structure of the forward and its position in relation to other parts of the monograph, the title as well as introductory and closing remarks. It has been discovered that Polish and German authors have a radically different approach to this type of text, though judging by the fact they call their texts forewords, these texts must belong to the same category.